Understanding the sexual and reproductive health [SRH] needs of adolescents and disabilities : a training manual for health care providers and counsellors (Mc CAM Child Development Centre KingstonJM, 2005)
Aims to heighten sensitivity to sexual and reproductive issues facing adolescents with disabilities.
Keywords: ADOLESCENT HEALTH